The Effect of Nature Education Activities on Biophilia Levels of Science Teacher Candidates - Abdurrahman Sefalı; Esra Ozay Kose (Journal of Science Learning, 2021)
As a result of increasing the level of interest in living and living systems (biophilia), it will be possible to educate more protectionist individuals against nature and the environment. This study was conducted to investigate the effect of nature education activities on biophilia levels of science teacher candidates. This research was conducted at public research university in Bayburt, Turkey, in the Department of Science Education during the spring semester of the 2017-2018 academic year. The activities were done in an integrated manner to the Environmental Science course. The study group included a total of 62 science teacher candidates. These students were distributed equally to the experiment and control group. The study was used a quasi-experimental method with a group of experiments and control. In the study, the Biophilia Scale was applied as a data collection tool. Independent samples t-tests and dependent samples t-tests were used for analyzing the data. As a result of the analysis, the findings indicated that nature education and in-class activities positively affected teacher candidates' biophilia levels. The findings also indicated that the knowledge and experience they gained due to students' scrutiny, touching, smelling, and even tasting the species at in-class and nature activities affected their biophilia levels.